Nanoparticle as a novel tool in hyperthermic intraperitoneal and pressurized intraperitoneal aerosol chemotheprapy to treat patients with peritoneal carcinomatosis - Nowacki, Maciej (Oncotarget, 2017)
The treatment of peritoneal surface malignances has changed considerably over the last thirty years. Unfortunately, the palliative is the only current treatment for peritoneal carcinomatosis (PC). Two primary intraperitoneal chemotherapeutic methods are used. The first is combination of cytoreductive surgery (CRS) and Hyperthermic IntraPEritoneal Chemotherapy (HIPEC), which has become the gold standard for many cases of PC. The second is Pressurized IntraPeritoneal Aerosol Chemotheprapy (PIPAC), which is promising direction to minimally invasive as safedrug delivery. These methods were improved through multicenter studies and clinical trials that yield important insights and solutions. Major method development has been made through nanomedicine, specifically nanoparticles. Here, we are presenting the latest advances of nanoparticles and their application to precision diagnostics and improved treatment strategies for PC. These advances will likely develop both HIPEC and PIPAC methods that used for in vitro and in vivo studies. Several benefits of using nanoparticles will be discussed including: 1) Nanoparticles as drug delivery systems; 2) Nanoparticles and Near Infrred (NIR) Irradiation; 3) use of nanoparticles in perioperative diagnostic and individualized treatment planning; 4) use of nanoparticles as anticancer dressing’s, hydrogels and as active beeds for optimal reccurence prevention; and 5) finally the curent in vitro and in vivo studies and clinical trials of nanoparticles. The current review highlighted use of nanoparticles as novel tools in improving drug delivery to be effective for treatment patients with peritoneal carcinomatosis.